Les avatars du «Prince grenouille» dans les traductions roumaines pour les enfants - Constantinescu, Muguras Albumita (Ondina - Ondine, 2018)
The avatars of the inaugural Grimm Brothers fairytale start from the title, where a translator chooses as solution La grenouille enchantée [Enchanted Frog], another Le Prince enchanté [Prince enchanted], another Le Prince Crapaud [Prince Toad] and, most often, we give up the second part of the title on Heinrich servant. As for the text of the tale, the metamorphoses are based on its publication - in the formula album – of one tale or in the collections of the Grimm Brothers, being generally more numerous in the former case when the dominant place went to the illustration. The initial place in the articulation of the tales is rarely kept in the collections, often selective, but preserved in the complete edition, supposed to address as to the skilled reader as to the school-age child. In the text of the story, we see several translators in the deletion of the sentence from the beginning about the vows that take place and the abbreviation of the end. Some additions and omissions by here and there are carriers of new connotations that reverberate in the imagination of the child. It also signals the introduction of some playful elements by the translator that puts in verses some replicas of the characters, the introduction of a pleasant nickname for the transformed prince, creating a gap with the original but can be an element of attractiveness to the small reader. Keywords: translation, title, initial place, omission-abbreviation, playful solutions.